Central and peripheral demyelination - Mehndiratta, Man Mohan (Medknow Publications & Media Pvt Ltd, 2014)
Several conditions cause damage to the inherently normal myelin of central nervous system, perepheral nervous system or both central and perepheral nervous system and hence termed as central demyelinating diseases, perepheral demyelinating diseases and combined central and perepheral demyelinating diseases respectively. Here we analysed and foccused on the etiology, prevalance, incidence and age of these demyelinating disorders. Clinical attention and various diagnostic tests are needed to adequately assess all these possibilities.